2018
DOI: 10.1002/humu.23598
|View full text |Cite
|
Sign up to set email alerts
|

Disruption ofTWIST1translation by 5′ UTR variants in Saethre-Chotzen syndrome

Abstract: Saethre‐Chotzen syndrome (SCS), one of the most common forms of syndromic craniosynostosis (premature fusion of the cranial sutures), results from haploinsufficiency of TWIST1, caused by deletions of the entire gene or loss‐of‐function variants within the coding region. To determine whether non‐coding variants also contribute to SCS, we screened 14 genetically undiagnosed SCS patients using targeted capture sequencing, and identified novel single nucleotide variants (SNVs) in the 5′ untranslated region (UTR) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…In this individual, we identified compound‐heterozygous variants c.1311G>A; p.W437* and c.‐38 T>A (Table ); the latter introduces an alternative ATG codon out‐of‐frame with the canonical start site. Such features in mRNA, also known as upstream open reading frames (uORFs), can cause widespread protein expression changes in humans, in some cases resulting in disease . We therefore speculated that c.‐38T>A might alter the amount of wild‐type LZTR1 protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this individual, we identified compound‐heterozygous variants c.1311G>A; p.W437* and c.‐38 T>A (Table ); the latter introduces an alternative ATG codon out‐of‐frame with the canonical start site. Such features in mRNA, also known as upstream open reading frames (uORFs), can cause widespread protein expression changes in humans, in some cases resulting in disease . We therefore speculated that c.‐38T>A might alter the amount of wild‐type LZTR1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis suggested that, while both sites have an equally strong identity with the [A/G]XXATGG Kozak consensus sequence, the novel ATG could have a higher reliability in initiating translation (Supplementary note 2). A reporter assay using a dual luciferase strategy was performed, as described . The ratio of renilla to firefly luciferase was consistently reduced to 77% to 85% for the mutant 5’‐UTR in comparison to the WT (Supplementary note 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5ʹUTR variants that alter uORFs have been described in association with the etiology of Mendelian disorders. Such variants may create an uAUG resulting in new uORF (Romanelli Tavares et al, 2019; von Bohlen et al, 2017; Wright et al, 2021; Zhou et al, 2018), or may disrupt the existing uORFs (Occhi et al, 2013; Wen et al, 2009). Analysis of allele frequency spectrum of variants in 15,708 individual whole‐genome sequencing data from the Genome Aggregation Database (gnomAD) reveals that uAUG‐creating variants and variants that disrupt uORF stop codons are under strong negative selection (Whiffin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%